2011
DOI: 10.1016/j.jval.2011.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Response Burden and Questionnaire Length: Is Shorter Better? A Review and Meta-analysis

Abstract: Given the inherently problematic nature of comparing questionnaires of various lengths, it is preferable to base decisions on use of instruments on the content rather than the length per se.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
485
1
8

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 639 publications
(504 citation statements)
references
References 43 publications
10
485
1
8
Order By: Relevance
“…Most important, the existing relevant scales partially overlap in content, yet individually they do not include all aspects of self-management relevant to the study, suggesting the need to complete several related questionnaires, which would significantly increase patient burden. 21 The scale used included 12 questions selected from the Stanford scale, the Diabetes Empowerment Scale, and the Chronic Illness Resources Survey. [22][23][24] The final questionnaire is available in Online Appendix 4.…”
Section: Measures Data Sources and Collection Methodsmentioning
confidence: 99%
“…Most important, the existing relevant scales partially overlap in content, yet individually they do not include all aspects of self-management relevant to the study, suggesting the need to complete several related questionnaires, which would significantly increase patient burden. 21 The scale used included 12 questions selected from the Stanford scale, the Diabetes Empowerment Scale, and the Chronic Illness Resources Survey. [22][23][24] The final questionnaire is available in Online Appendix 4.…”
Section: Measures Data Sources and Collection Methodsmentioning
confidence: 99%
“…It is however recognised that the completion of questionnaires can be burdensome for participants. 93 This may be particularly the case for those with few or no symptoms; this may account for the number of blank questionnaires returned at 6 months, and was apparent from the patient interview study. Accepting that the UDI was the fourth instrument in a booklet of 6 questionnaires in total, it had a slightly lower completion rate at both baseline and 6 months.…”
Section: Key Messagesmentioning
confidence: 99%
“…a non-paper-based questionnaire) was feasible to administer and generally acceptable to participants. Much has been written about the associations between length of questionnaire and response rates; [191][192][193] some participants in our study found the questionnaire to be too long. Nevertheless, 'how long is too long' is likely to be subjective, and face-to-face administered surveys lasting over 1 hour have been found to be acceptable in some studies.…”
Section: Feasibility and Acceptability Of Trial Proceduresmentioning
confidence: 89%